IMPLEMENTASI SISTEM INFORMASI MANAJEMEN (SIM) BIDANG AKADEMIK DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN - Riani, Vanisha Amelia; Trisnantari, Hikmah Eva; Junaris, Imam (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
The use of technology, particularly in the form of Academic Management Information Systems (SIM), has become a necessity for educational institutions. The implementation of SIM in the academic field helps to simplify the administration, processing, and storage of important academic data. This article aims to explore the implementation of SIM in enhancing the quality of services in educational institutions. The research method used is a literature review, examining 5 national journals and 5 international journals from 2020-2023. The findings indicate that SIM has been utilized by educational institutions at various levels, from elementary schools to universities. The use of SIM is driven not only by the demands of the times but also by the various conveniences it offers institutions in managing, organizing, storing, and presenting data quickly and accurately, thus enhancing the quality of educational services.